The Influence of Infrastructure and Teacher’s Work Motivation on Student’s Learning Achievement (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This research aims to determine the influence of infrastructure and student learning motivation on the learning achievement of SMPN 01 Jayapura OKU Timur. This type of research is quantitative research with a research design using an ex post facto research design. The sample in this study were students of SMPN 01 Jayapura, East OKU Regency, class IX, and class VIII groups A-C, totaling 114 students. The data collection technique used a questionnaire. Data analysis techniques use quantitative descriptive analysis techniques and multiple regression. The results of this research state that there is there is significant influence partially and jointly between infrastructure and teacher’s work motivation on student’s learning achievement at SMPN 01 Jayapura OKU Timur. It implies to all stakeholders of education in Indonesia to pay more attention toward infrastructure and work motivation to gain good student’s learning achievement.